1959
DOI: 10.1161/01.cir.20.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Kidney in the Pathogenesis of Congestive Heart Failure

Abstract: The pathogenesis of sodium retention in congestive heart failure has been a difficult problem to elucidate. The production in dogs of cardiac valvular lesions of increasing severity has enabled investigators to study the sequential alterations in salt and water balance in the same animal from the normal state through the progressive stages of cardiac impairment until frank failure is present. The findings in dogs suggest that: 1. Abnormalities in sodium metabolism are detectable in mild heart disease long befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

1962
1962
2003
2003

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(38 citation statements)
references
References 22 publications
3
34
1
Order By: Relevance
“…In addition, it would avoid the offsetting antinatriuretic influence of the decrease in arterial pressure that occurs with blockade of systemic ␣ 1 -adrenoceptors. This recapitulates the important experiment of Barger, 37,38 in which unilateral renal denervation in CHF dogs resulted in an ipsilateral diuresis and natriuresis without changes in RBF, GFR, or arterial pressure. It also focuses on increased RSNA as one of the contributing factors to the defect in renal sodium excretory capacity so fundamental to a prevailing concept of the development of hypertension.…”
Section: The Futuresupporting
confidence: 81%
“…In addition, it would avoid the offsetting antinatriuretic influence of the decrease in arterial pressure that occurs with blockade of systemic ␣ 1 -adrenoceptors. This recapitulates the important experiment of Barger, 37,38 in which unilateral renal denervation in CHF dogs resulted in an ipsilateral diuresis and natriuresis without changes in RBF, GFR, or arterial pressure. It also focuses on increased RSNA as one of the contributing factors to the defect in renal sodium excretory capacity so fundamental to a prevailing concept of the development of hypertension.…”
Section: The Futuresupporting
confidence: 81%
“…The enhanced sympathetic tone under these circumstances is believed to contribute to improved cardiac performance by increasing the heart rate and myocardial contractility, thereby sustaining perfusion to vital organs (39). It has been experimentally demonstrated that the antidiuresis and antinatriuresis induced by constriction of the thoracic vena cava or tricuspid insufficiency in dogs was abolished by pretreatment with systemic or intrarenally administered adrenergic blockers (40)(41)(42)(43) or, as in the present study, surgical denervation (43)(44)(45). In some of these studies, whole kidney plasma flow rate, estimated by renal clearance of para-aminohippuric acid, was found to change to a relatively small and variable degree after the adrenergic inhibition (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Since all of the cases who responded to the aldosterone antagonist did not excrete increased amounts of aldosterone metabolites in urine, the authors suggested that a reduced rate of removal from plasma may have increased the circulating level of hormone. Further work will be necessary to evaluate other factors that sensitize the animal with congestive failure to the sodium-retaining effect of adrenal steroids (31,32).…”
Section: Methodsmentioning
confidence: 99%